A few remarks on relative ergodic properties of C*-dynamical system - Duvenhage, Rocco; Mukhamedov, Farrukh (American Institute of Physics, 2015)
We study various ergodic properties of C*-dynamical systems inspired by unique ergodicity. In particular we work in a framework allowing for ergodic properties defined relative to various subspaces, and in terms of weighted means